(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2019)
This paper presents a study that aims at identifying the frequency and typology of Spanish phraseological units (PUs) used in spontaneous informal language production. For this kind of study, it is necessary to have access to spontaneous, free-spoken conversations. The source of the PUs for this research is formed by conversations extracted from Gran Hermano, the Spanish version of Big Brother. In this study data obtained from the analysis of almost two hours of spontaneous conversations extracted from Gran Hermano 16 (broadcast live 24/7 via on-line streaming) will be presented and discussed. Moreover, it is intended to open up for discussion whether this reality show can be a better source of spontaneous informal conversations than the existing Spanish oral corpora.